Central bank intervention and exchange rates: The case of Sweden - Javiera Aguilar; Stefan Nydahl (Sveriges Riksbank, 1998)
This paper examines the effect of the Riksbank's currency market interventions on the level and the volatility of the USD/SEK and DEM/SEK exchange rates between 1993 and 1996. To model volatility both GARCH models and implied volatilities from currency options are used. Some support is found for the idea that interventions affect the exchange rate level during certain sub periods but overall the results are weak. Furthermore, in line with the findings for other countries, little empirical support is found for the hypothesis that central bank intervention systematically decreases exchange rate volatility.
Keywords: 330